Structure of Population Assiminea brevicula Associate with Mangrove Vegetation in Poton Bako Bay, South Coast East Lombok - Tita Syahri Ramadhani; Abdul Syukur; Muhammad Yamin; Didik Santoso (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Research on the population structure of Assiminea brevicula associated with mangrove vegetation in Poton Bako Bay, South Coast of East Lombok was conducted in June 2023. This study aims to determine population structure, population density, distribution patterns and the length-weight relationship of Assimineea brevicula gastropods associated with Poton Bako mangrove vegetation, South Coast of East Lombok. Data collection was carried out using the quadratic method using purposive sampling by taking into account the mangrove species found in the observation plots. As a result, the frequency of the number of Assiminea brevicula gastropods in relation to the shell length of the samples was in the size range of 6 mm - 7 mm. The maximum shell length obtained was 10 mm. From the data obtained, the highest density figure during the research was located at station 3, namely 8.24 ind/m2. The population distribution pattern of Assiminea brevicula in Poton Bako is clustered, uniform, and random with a dominant cluster pattern. The length-weight relationship on June 11 2023 obtained the equation W = 0.18L1.04 and on June 18 2023 obtained W = 0.68L0.31, and on June 25 2023 with the equation W = 0.067L1.48 because slope < 3, with a thin shape, the nature of growth is negative allometric, which means that the increase in length of the snail is faster than the increase in weight.